2004
DOI: 10.1088/0957-4484/15/9/035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanomorphology on the photovoltaic action of polymer–fullerene composites

Abstract: Composites of conjugated poly(3-hexylthiophene) (P3HT) and the fullerene derivative [6,6]-phenyl-C 61 butyric acid methyl ester (PCBM) demonstrate an efficient photogeneration of mobile charge carriers. Thermal annealing of P3HT:PCBM based devices gives rise to a significant increase of the photovoltaic efficiency, as follows from measurements of the external quantum efficiency and the current-voltage characteristics. Upon annealing, the absorption spectrum of the P3HT:PCBM composite undergoes a strong modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
541
3
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 715 publications
(584 citation statements)
references
References 27 publications
33
541
3
7
Order By: Relevance
“…This peak corresponds to the a-axis orientation, with the main polymer chain parallel and the side chains perpendicular to the substrate [29]. It is observed that the films annealed at different temperatures in air and Ar atmospheres result in improved diffraction peaks, indicating an improvement of the degree of crystallization of the P3HT structure [30]. However, annealing at higher temperature (150 °C) demonstrated a decrease in the diffraction peaks of both films annealed in air and Ar atmospheres due to a slight disordering in the P3HT structure.…”
Section: Results and Discussion X-ray Diffractionmentioning
confidence: 93%
“…This peak corresponds to the a-axis orientation, with the main polymer chain parallel and the side chains perpendicular to the substrate [29]. It is observed that the films annealed at different temperatures in air and Ar atmospheres result in improved diffraction peaks, indicating an improvement of the degree of crystallization of the P3HT structure [30]. However, annealing at higher temperature (150 °C) demonstrated a decrease in the diffraction peaks of both films annealed in air and Ar atmospheres due to a slight disordering in the P3HT structure.…”
Section: Results and Discussion X-ray Diffractionmentioning
confidence: 93%
“…Previous research has shown that high regio-regular (RR) P3HT performs better in BHJ solar cells, 36 due, in part, to the strong interchain interactions, which leads to better absorption and structural order, resulting in a higher hole-mobility. It was also observed that when the P3HT:PCBM blend ratio is $1:1 or 1:0.8, the blends gave the best device performance, 37,38 due, in part, to the ease in forming a cocontinuous morphology. Yet, processing conditions and postprocessing treatments will also largely affect the device performance.…”
Section: Morphology Study Based On P3htmentioning
confidence: 98%
“…A substantial improvement in the PCE of P3HT:PCBM based solar cells has been obtained by thermal annealing at around 140 1C, and the favourable influence of annealing on blend film microstructure and solar cell performance is well documented. [50][51][52][53] The mechanism by which current density and PCE increase upon thermal annealing in P3HT:PCBM is not known precisely but it is believed to involve increased optical absorption and improved charge transport, both due to polymer crystallization, as well as improved charge pair separation efficiency, due to optimized phase segregation. Some of the literature is reviewed below.…”
Section: Thermal Annealingmentioning
confidence: 99%